An Update on the Study of the Double Motif (Doppelgänger) in Fantastic Literature - Argüelles Fernández, Gerardo (2024)
Various interpretations of the phenomenon of the double in fantastic literature are often substantiated with the help of the clinical literature on autoscopic depersonalization. In this contribution, however, the intention is to point out that, for these reasons, the actual literary motif of the Doppelgänger has not been exhaustively analyzed following the particular hermetic and hermeneutic strengths established with every intention by the author who creates obviously fantastic literature and who, therefore, has to demand from his readers the performance of a fictional allegiance to that singular exposition of the life-world experience of the human being. Here and with the aid of theorists such as R. Lachmann, H.-J. Gerigk and Chr. Forderer, it is our hypothesis that the motif of the fantastic double in literature can be studied without the clinical disciplines in order to discover the plausible paradoxes of the splitting of an individuality; all this with the support of the fact that, what medical science cannot fully understand and explain, literature makes it a narrative argument, reveals its details and makes it spiritually comprehensible on the basis of a perfectly plausible life world (Lebenswelt).